The Role of Job Satisfaction in Mediating Between Work Life Balance and Employee Well Being on Employee Performance at PT Petrosea - Vindy Widia Agustianis; Djoko Soelistya; Mog. Agung Surianto (Al-Kharaj: Journal of Islamic Economic and Business, 2024)
This study uses a quantitative method, with a sample of 167 respondents analyzed through the SmartPLS program. The findings are as follows: (1) work-life balance has a direct effect on employee performance; (2) employee well-being has a direct effect on employee performance; (3) work-life balance has a direct effect on job satisfaction; (4) employee well-being has a direct effect on job satisfaction; (5) job satisfaction has a direct effect on employee performance; (6) job satisfaction is not needed as a mediator, as the direct effect of work-life balance is more dominant than the indirect effect, indicating partial mediation; and (7) job satisfaction is also not needed as a mediator, as the direct effect of employee well-being is more dominant than the indirect effect.